3D-printed thermoplastic composite fasteners for single lap joint reinforcement. (15th February 2022) - Li, Wenhao; Guo, Shijun; Giannopoulos, Ioannis K.; Lin, Minxiao; Xiong, Yi; Liu, Yiding; Shen, Zhengquan
Abstract: This study presents findings for the strength and failure mechanism of a 3D-printed Continuous Carbon Fibre reinforced Onyx (CCF/Onyx) Thermo-Plastic Composite Fastener (TPCF) and a single lap-joint (SLJ) made of fibre/polymer composite reinforced by the TPCF. The study was carried out by numerical analysis and experiment methods including test sample design, manufacturing process and mechanical test. The 3D-printed fasteners were manufactured and tested in shear mode for two types of joining arrangement: fastened and hybrid bonded/fastened joints. Firstly, experiment was carried out for the TPCF fastened SLJ and the results show that addition of CCF in the Onyx matrix and post heat-treatment process could significant enhance the TPCF strength. The results was then benchmarked against a SLJ with steel fastening. The shear failure load of the SLJ reinforced by heat-treated CCF/Onyx TPCF of 8 mm diameter was 36% lower than a SLJ reinforced by a steel bolt of the same size. Numerical model for progressive damage simulation was also created based on the failure theory from Puck and Schürmann achieving good correlation with the experimental data. Secondly, the TPCF fasteners were manufactured with two types of heat-treated countersunk head and pan head forming and used to reinforce bonded SLJ. The test results show that the bonded SLJ reinforced by the TPCF fastener of countersunk head is of 11.7% higher strength and an increase in ultimate deformation by 9.1% compared to a bonded SLJ reinforced by steel fastener of 5 mm diameter. From the numerical and experimental study, it was noted that this was attributed to countersunk configuration to reduce out-out-plane bending and provide better crack arresting for the joint bonding.